2019
DOI: 10.1097/01.ogx.0000554051.64539.4d
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality After Cesarean Section in the Netherlands

Abstract: Maternal mortality after cesarean section in the Netherlands Athanasios F. Kallianidis, Joke M. Schutte, Jos van Roosmalen, Thomas van den Akker. Objectives: Maternal mortality is rare in high-resource settings. This hampers studies of the association between maternal mortality and mode of birth, although this topic remains of importance, given the changing patterns in mode of birth with increasing cesarean section rates in most countries. Purpose of this study was to examine incidence of cesarean sectionrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
2
10
1
Order By: Relevance
“…This is comparable with ndings of a systematic review and meta-analysis conducted in low-and middle-income countries where the risk of maternal death in women who had CS was 7.6 per 1000 women (10.9 per 1000 women in sub-Saharan Africa) 46 . Although the risk of maternal death is usually higher after CS than after vaginal birth both in low 46 and high income 11,47 countries, the magnitude was greater in our study than in most previous studies. This may be because this study included only hospitals with data where complicated cases are managed while vaginal births can be provided at lower level facilities.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This is comparable with ndings of a systematic review and meta-analysis conducted in low-and middle-income countries where the risk of maternal death in women who had CS was 7.6 per 1000 women (10.9 per 1000 women in sub-Saharan Africa) 46 . Although the risk of maternal death is usually higher after CS than after vaginal birth both in low 46 and high income 11,47 countries, the magnitude was greater in our study than in most previous studies. This may be because this study included only hospitals with data where complicated cases are managed while vaginal births can be provided at lower level facilities.…”
Section: Discussioncontrasting
confidence: 78%
“…A report of the WHO global survey conducted in nine Asian countries also showed that higher rates of CS were associated with higher MMR 9 . A similar nding was reported in the Netherlands, a high-income country 11 . The higher rate of maternal deaths after CS as compared to vaginal delivery may be attributed to postpartum haemorrhage, complications of anaesthesia and postoperative sepsis 12,13 .…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…A report of the WHO global survey conducted in nine Asian countries also showed that higher rates of CS were associated with higher MMR [9]. A similar finding was reported in the Netherlands, a high-income country [11]. The higher rate of maternal deaths after CS as compared to vaginal delivery may be attributed to postpartum haemorrhage, complications of anaesthesia and postoperative sepsis [12,13].…”
Section: Introductionmentioning
confidence: 67%
“…The incidence of maternal mortality after CS in developed countries (USA) is 13.3 per 100,000 inhabitants, while in vaginal delivery the incidence is 3.6 per 100,000. General incidence of severe complications associated with CS is 9.2%, with total maternal mortality being 2.7% [6,16,17,18]. During the three-year period (2013-2015) there were no lethal outcomes after CS at the Clinic of Gynecology and Obstetrics, Clinical Center of Serbia in Belgrade.…”
Section: Discussionmentioning
confidence: 97%